3x-y-3=0;4x-y-8=0 by elimination method
Answers
Hope you will mark me as the brainiest
![](https://hi-static.z-dn.net/files/da8/a46a4429121b188bcb151ff2b92369c5.jpg)
Answer:
x = 5 and y = 12
Step-by-step explanation:
In the elimination method, you have to write down both the equations, one below the other, like this:
3x - y - 3 = 0
4x - y - 8 = 0
Now, you have to subtract the equations:
3x - y - 3 = 0
- 4x - y - 8 = 0
----------------------
-x + 0y + 5 = 0
So,
The answer is -x + 0 + 5 = 0
=> -x + 5 = 0
=> -x = -5
=> x = 5
Given in the question,
3x - y - 3 = 0
Since we now know that x = 5, we can substitute the value of x in the above equation.
3x - y - 3 = 0
3(5) - y - 3 = 0
15 - y - 3 = 0
(15 - 3) - y = 0
12 - y = 0
- y = - 12
y = 12
Therefore, x = 5, and y = 12